Three Essays on Behavioural Finance in Shipping Markets - Melas, Konstantinos (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2019)
Shipping finance is a strand of literature that was mainly initiated by Costas Grammenos and its main driver was the need of shipowners and ship operators to manage the financial aspect of the sector given the volatility that it is always apparent. The research that has been conducted up to now focuses on examining aspects relevant to the assets (ships) and the freight rates (cash flow). Despite the work that has already been conducted all these years, the financial crisis of 2008 re-enforced the need to develop a better understanding of the complexities of the external and the internal drivers of the shipping industry. In the current thesis, three topics that are of prime importance to the industry have been researched in order to address certain unanswered questions. More precisely, the volatility spillovers of the freight rates, corporate governance of the shipping companies and sales and purchases of second-hand dry bulk carriers have been examined. Chapter 1 explores the determinants of investment diversification in the shipping industry, as measured by the net volatility spillover index introduced by Diebold & Yilmaz (2012) and in the shipping context by Tsouknidis (2016). Specific indicators of shipping economic activity as introduced in Papapostolou et al. (2016) are used as potential determinants of the net volatility spillover indices across the dry bulk and tanker shipping segments and sub-segments. Results reveal that certain measures of investment prospects and activity in the second-hand vessels market are positively associated with increased volatility spillovers across shipping segments. Chapter 2, reviews the role of corporate governance in maritime enterprises. While various research has been conducted on the executive teams of shipping companies and their relationship with the companies’ performance, results, however, remain inconclusive on the specific characteristics that are having a positive influence on the companies’ performance. In the current research, we have employed the largest sample that has been used up to now and we are examining the relation between the demographic characteristics of the board of directors with the financial performance of the shipping companies. Nevertheless, given the volatility that exists in the shipping market, we further examine the demographic characteristics that are particularly important when the market participants are either overly optimistic or overly pessimistic for the outlook of the market. In this chapter, a literature review of the relevant bibliography reveals the unique characteristics of the shipping industry as far as corporate practices and their outcomes are concerned. Moreover, the chapter discusses how corporate governance affects enterprises at large and why both academics and professionals have been active in the field, trying both to grasp the conundrum of corporate boards, and additionally to create ameliorating policies. Finally, exploratory research is conducted to reveal the demographic profile of the corporate boards. The revealed trends of the last 15 years provide the reader with insight of the practices that maritime enterprises have been using in order to provide better mechanisms of governance. Chapter 3, re-examines the methods for vessel valuation and the predominant factors that affect them. Given the diffusion of information that derives from recent technological advances, we further test previous models with an updated and more thorough dataset. Accordingly, evidence on the significance of the different level of information when compared to annual averages is provided. Additionally, we further enhance the existing literature by adding an extrapolating variable that accounts for the profitability of vessels. Thus, we employ a statistical technique, based on the precise age of a vessel, to capture the total profit that she will provide until she is demolished. The estimation provides results that reduce the variance between the actual transaction prices and the predicted ones when compared to benchmark models by 20%.
Keywords: Shipping; Maritime; Finance; Management